2017
DOI: 10.15406/mojwh.2017.05.00114
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Outcome in Rhesus Positive Women in a Tertiary Care Center

Abstract: Background: Incidence of Rh negativity in India ranges from 3-5.7%. Rh negative pregnancy not only poses risk to mother but in the fetus, may lead to dreaded complication like hemolysis and intrauterine fetal demise. However, the advance management and early detection of the condition can prevent the complication. Objective: This study aims to determine the prevalence of Rh negative pregnancy in our population, to study the various maternal and fetal complications. Materials and methods: A retrospective review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
4
1
Order By: Relevance
“…In our study the incidence of Rh-negative pregnancy was 2.9 % which is similar to the national average of 3% to 5%. Which was comparable to the study done by [9][10][11][12][13] The prevalence in our study was higher than other studies because our center is tertiary referral center. In Table 2, our study was comparable according to parity, Agarwal et al who found 38.4% primigravida 33.6% second gravid 20% third gravid and 8% were multigravida.…”
Section: Discussionsupporting
confidence: 90%
“…In our study the incidence of Rh-negative pregnancy was 2.9 % which is similar to the national average of 3% to 5%. Which was comparable to the study done by [9][10][11][12][13] The prevalence in our study was higher than other studies because our center is tertiary referral center. In Table 2, our study was comparable according to parity, Agarwal et al who found 38.4% primigravida 33.6% second gravid 20% third gravid and 8% were multigravida.…”
Section: Discussionsupporting
confidence: 90%
“…This finding agreed with a study from Bangalore India reporting that the most common blood group among Rh-negative women was O-negative. 34 However, this finding was lower than that previously reported from India, blood group B 33.96% and blood group O 32.62%, but much higher than blood group A and AB reported 24.35% and 9.05%, respectively. 31 The difference could be due to blood group O being the predominant blood group among the African population compared to other continents.…”
Section: Discussioncontrasting
confidence: 62%
“…35 The current finding is higher than that of a study performed in Bangalore India, which reported 8.33%. 34 On the other hand, the result of the study was much lower than that of neonatal jaundice, which was 37.2% in Rajavithi Hospital. 33 In hospital medical records, the absence of different risk factors may contribute to the appearance of jaundice, such as ABO incompatibility, obstructive jaundice or physiologic jaundice; hence, it is difficult to assess the causes of neonatal jaundice.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…To overcome such fetal danger, anti-D injection is required for the mother within 72 hours after the first delivery. The anti-D injection will help the mother to get rid of any blood that has leaked from the first fetus during childbirth so that her blood will not produce antibodies, which could affect the next pregnancy [20][21][22][23][24].…”
Section: Blood Group Test For Newly Married Couplesmentioning
confidence: 99%